Status of Periodontal Tissues in Patients with Diseases of the Oral Mucosa - Kolenko Ю. Г.; Mialkivskyi К. О. (Actual Dentistry, 2024)
Actuality. There is an axis of interaction between periodontitis and some oral mucosa lesions. For example, generalized periodontitis is closely related to lichen planus, a chronic inflammatory condition caused by an autoimmune disorder (i.e., the immune system mistakenly attacks the cells of the oral mucosa). The aim was to investigate the relationship between oral mucosa and periodontal diseases. Materials and methods. In 2024, 65 people aged 21–75 applied for examination and rehabilitation at the Department of Therapeutic Dentistry of the Bogomolets National Medical University. The main study group consisted of 49 people with oral mucosa diseases. The control group consisted of 16 patients with periodontal diseases. The main group consisted of 19 patients with a preliminary diagnosis of leukoplakia, 10 patients with a preliminary diagnosis of oral cancer, 7 patients with a preliminary diagnosis of papilloma, and 13 patients with a preliminary diagnosis of lichen planus. The assessment of the clinical oral health status of the patients included the diagnosis of the main indicators of the oral cavity and periodontal screening with the determination of clinical indices. Statistical analysis of the data obtained was performed using a personal computer with the application software Microsoft Excel 2021, StatSoft Statistica 12. Results of the study and discussion. The prevalence of periodontal diseases among the patients of the main group was distributed as follows: 10 people (20.4%)—with gingivitis: dental biofilm induced; 24 people (49.0%)—with periodontitis I stage; 15 people (30.6%)— with periodontitis II stage. The prevalence of periodontal disease in the control group was as follows: 3 people (18.8%)—with periodontal and gingival health; 7 people (43.7%)—with gingivitis: dental biofilm induced; 4 people (25.0%)—with periodontitis I stage; 2 people (12.5%)—with periodontitis II stage. The mean value of CPV in the main group was 21.65 ± 8.46, in contrast to the control group, where it was 14.18 ± 8.26. In the main group of patients, the mean value of the Silnes-Loe index was 2.86 ± 0.19 points, corresponding to unsatisfactory hygiene (p < 0.05). In the control group, this index was 1.18 ± 0.26 (p < 0.05). Conclusions. Poor oral hygiene and subsequent plaque accumulation lead to a chronic inflammatory process in the periodontal tissues, creating an environment conducive to the development of precancerous and malignant oral lesions. It has been established that periodontitis is an individual risk factor for the development of precancerous and malignant lesions of the oral cavity.